RELATIONSHIP BETWEEN KNOWLEDGE LEVELS AND EFFORTS TO PREVENT GASTRITIS RECURRENCE AMONG TEENAGERS IN RW 006 OF SEPANJANG JAYA, RAWALUMBU DISTRICT IN 2022 - Parameswari, Nadieva Nailuvar Jasmine; Bunga, Dinda Nur Fajri Hidayati; Meliyana, Ernauli (Rena Cipta Mandiri, 2025)
Gastritis is a disease that often triggers recurrence. One of the factors that cause recurrence is the patient's lifestyle as a result of lack of knowledge in preventing the recurrence of gastritis. Busy activities at school, dense social activities, and a strict diet to maintain appearance are common characteristics of lifestyle mistakes among teenagers. Lack of knowledge and understanding of unhealthy lifestyles causes gastritis in them. This research was conducted using a quantitative method. The design in this study used Analytical Observation with a Cross Sectional approach. The research sample consisted of 51 teenagers aged 14 -19 years in RW 006 who were selected using purposive sampling technique. Bivariate analysis was carried out through the Chi Square statistical test. A p-value of (0.000) < (0.05) was obtained. This shows that Ho is rejected and Ha is accepted. The results of the bivariate analysis showed 42 respondents had a good level of knowledge, with 34 respondents (66.7%) aware of relapse prevention efforts. Based on the results of the study, there is a significant relationship between the level of knowledge and efforts to prevent recurrence of gastritis among teenagers in RW 006 of Sepanjang Jaya, District Rawalumbu in 2022.